A modified Malecot catheter design to prevent complications during difficult percutaneous nephrostomy. Issue 4 (2nd October 2019) - Sonawane, Parag; Ganpule, Arvind; B, Sudharsan; Singh, Abhishek; Sabnis, Ravindra; Desai, Mahesh
ABSTRACT: Objective : To demonstrate the feasibility of using a modified Malecot catheter with a proximal end adapter as compared to the conventional Malecot catheter, and demonstrate the technique of performing a contrast study without removing the guidewire (GW). Patients and Methods : A modified 14-F Malecot catheter with a new proximal end connector with one side channel was used for percutaneous nephrostomy (PCN) under fluoroscopy guidance in five patients. The modified Malecot catheter was introduced over the GW under fluoroscopy guidance. The contrast study was done using the side channel of the connector whilst the GW was in situ through the main channel. Five senior urologists were asked to assess the modified Malecot catheter by rating their experience on a 5-point Likert scale, which had three items. In a further five patients, the same urologists performed PCN using a conventional Malecot catheter and again rated their experience on the same Likert scale. Results : Total procedure time, fluoroscopy time, and ease of insertion were comparable in the two groups; however, the ease of the contrast study, security of correct positioning, and overall assessment were reported to be better with the modified Malecot catheter. Conclusion : The modified Malecot design allows for easy percutaneous access comparable to the conventional Malecot catheter, with the advantages of ease of performing a contrast study and better security of correct positioning. Abbreviations: GW: guidewire; PCN: percutaneous nephrostomy; PCS: pelvicalyceal system